Efeito da Mentha piperita L. durante a infecção experimental por Schistosoma mansoni - Zaia, Mauricio Grecco (2015)
Schistosomiasis is a parasitic disease caused by several species of trematode worms and it is believed that more than 249 million people are affected worldwide, with 700 million people living in risk areas. In Brazil, only the Schistosoma mansoni is found as the etiologic agent of schistosomiasis, responsible for more deaths than dengue, visceral leishmaniasis and malaria in the country. Currently, there is only one drug indicated for the treatment of schistosomiasis (Praziquantel) and the development of new drugs has become essential due to parasite resistance risk against this drug. Thus, this study aimed to evaluate the parasitological, immunological and histological profile in infected mice with Schistosoma mansoni, after treatment with an herbal business, consisting of menthol (30-55%) and menthone (14-32%), prepared from the leaves of Mentha piperita L. In addition, we evaluated the possible genotoxic effect of the herbal in cells of adult worms recovered from these treated animals using the comet assay technique. Female BALB/c mice were divided into 6 groups: Negative Control, Positive Control, Mentha 15, Mentha 60, PZQ and Cremophor. Each animal was infected with 80 cercariae of Schistosoma mansoni and treated 60 or 15 days with the herbal test. Single dose of 400 mg/kg of Praziquantel to PZQ group was administered. The animals were killed 61 days after the infection, in which were evaluated the cellular profile (total and differential counts of blood leukocytes and peritoneal cavity lavage), immune profile (IL-10, IL-4 and IFN -ɤ measurement by ELISA) and histological profile of liver and intestine of treated mice. Kato-Katz's technique was performed for quantifying eggs/gram at 45 and 60 days after infection and carried out adult worms recovered by perfusion of the hepatic portal system. Statistical analysis was performed using GraphPad Prism 5 (2005), using the non-parametric test (One-way ANOVA) through the analysis of variance (Tukey), considering p<0.05. The results showed that both groups treated with the herbal alter the behavior of the infection. The longer treatment with herbal (Mentha 60) decreased the number of S. mansoni eggs in the feces, liver and intestine of mice and reduced the number of hepatic granulomas, when compared to the Positive Control. In the same group was observed a reduction of blood eosinophils (84%) and a decrease the IL-4 and IL-10 levels when compared to the Positive Control, indicating a probable immunomodulation in this experimental infection model. Treatment with herbal medicine has no genotoxic effect on adult worms of S. mansoni in this model. Therefore, it is suggested that treatment with the herbal medicine for a long time, consisting of menthol and menthone, prepared from leaves of Mentha piperita L., has an immunomodulatory and anti-inflammatory action in this experimental model of murine schistosomiasis mansoni, contributing to the decrease in pathological effects caused by infection with S. mansoni.